Habitability on planetary surfaces: interdisciplinary preparation phase for future Mars missions - Peeters,Z; Quinn,R; Martins,Z; Sephton,MA; Becker,L; van,Loosdrecht MCM; Brucato,J; Grunthaner,F; Ehrenfreund,P (INT J ASTROBIOL, 2009)
Life on Earth is one of the outcomes of the formation and evolution of our solar system and has adapted to every explored environment on planet Earth. Recent discoveries have shown that life can exist in extreme environments, such as hydrothermal vents, in deserts and in ice lakes in Antarctica. These findings challenge the definition of the ‘planetary habitable zone’. The objective of future international planetary exploration programmes is to implement a long-term plan for the robotic and human exploration of solar system bodies. Mars has been a central object of interest in the context of extraterrestrial life. The search for extinct or extant life on Mars is one of the main goals of space missions to the Red Planet during the next decade. In this paper we describe the investigation of the physical and chemical properties of Mars soil analogues collected in arid deserts. We measure the pH, redox potential and ion concentrations, as well as carbon and amino acid abundances of soils collected from the Atacama desert (Chile and Peru) and the Salten Skov sediment from Denmark. The samples show large differences in their measured properties, even when taken only several meters apart. A desert sample and the Salten Skov sediment were exposed to a simulated Mars environment to test the stability of amino acids in the soils. The presented laboratory and field studies provide limits to exobiological models, evidence on the effects of subsurface mineral matrices, support current and planned space missions and address planetary protection issues.